2015
DOI: 10.3389/fncel.2015.00413
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of post Status Epilepticus treatment with ROCK inhibitor Y-27632 in a pilocarpine model of temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is the most common type of epilepsy in adults where 20–30% of the patients are refractory to currently available anti-epileptic drugs. The RhoA/Rho-kinase signaling pathway activation has been involved in inflammatory responses, neurite outgrowth and neuronal death under pathological conditions such as epileptic insults. Acute preventive administration of ROCK inhibitor has been reported to have beneficial outcomes in Status Epilepticus (SE) epilepsy. In the present study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…ROCK/PKA inhibitors such as Y-27632 and Fasudil have already been successfully used in Ophn1-dependent form of intellectual disability (Meziane et al, 2016;Compagnucci et al, 2016;Redolfi et al, 2016;Allegra et al, 2017). Moreover, these compounds have also shown anticonvulsant effects in specific seizure models (Inan et al, 2008;Kourdougli et al, 2015;Çarçak et al, 2018), suggesting that they could be employed as an adjuvant or alternative therapy for refractory epilepsy. Here, based on in vitro results (Powell et al, 2012), we first investigated whether a single pharmacological treatment could abolish the enhanced excitability in Ophn1 KO mice in vivo, and we found that such treatment was not effective (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK/PKA inhibitors such as Y-27632 and Fasudil have already been successfully used in Ophn1-dependent form of intellectual disability (Meziane et al, 2016;Compagnucci et al, 2016;Redolfi et al, 2016;Allegra et al, 2017). Moreover, these compounds have also shown anticonvulsant effects in specific seizure models (Inan et al, 2008;Kourdougli et al, 2015;Çarçak et al, 2018), suggesting that they could be employed as an adjuvant or alternative therapy for refractory epilepsy. Here, based on in vitro results (Powell et al, 2012), we first investigated whether a single pharmacological treatment could abolish the enhanced excitability in Ophn1 KO mice in vivo, and we found that such treatment was not effective (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammation could have several effects, among which, cell-death is one of the most prominent effects. It has been shown in other models that inflammation is associated with a massive loss of hippocampal formation write in epilepsy (Aldenkamp and Bodde, 2005; Swartz et al, 2006; Jefferys, 2010; Peng et al, 2013) or TBI models (Swartz et al, 2006; Morrison et al, 2011; Belousov et al, 2012; Acosta et al, 2013) and more particularly in the DG region (Lowenstein et al, 1992; Kourdougli et al, 2015; Sun et al, 2015). In that context, neuronal cell death and more specifically Parvalbumin positive cell death is one particular phenomenon both in epilepsy (Huusko et al, 2015) and in TBI models (Santhakumar et al, 2001; Cantu et al, 2014; Huusko and Pitkänen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypes resulting from the knockout of the mammalian TGF‐β isoforms are very distinct (reviewed in Dünker & Krieglstein, 2000). We have recently shown that TGF‐β2 regulates functional expression of the neuronal K + /Cl ‐ cotransporter 2 (KCC2) (Roussa et al, 2016), a molecular component increasingly appreciated in the context of epilepsy (Kelley et al, 2016; Kourdougli, Varpula, Chazal, & Rivera, 2015). We have hypothesized that TGF‐β2 is the isoform required for 4AP‐dependent NBCe1 regulation.…”
Section: Discussionmentioning
confidence: 99%